A Reference Direction Algorithm for Solving Multiple Objective Integer Linear Programming Problems - Vassilev, Vassil; Narula, Subhash C. (The Journal of the Operational Research Society, 1993)
In this paper, we propose a reference direction approach and an interactive algorithm to solve the general multiple objective integer linear programming problem. At each iteration, only one mixed integer linear programming problem is solved to find an (weak) efficient solution. Each intermediate solution is integer. The decision maker has to provide only the reference point at each iteration. No special software is required to implement the proposed algorithm. The algorithm is illustrated with an example.